2020
DOI: 10.3390/ma13030588
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage and Mechanical Properties of Self-Compacting SFRC With Calcium-Sulfoaluminate Expansive Agent

Abstract: With the premise of ensuring workability on a fresh mixture, the volume stability of hardened self-compacting steel fiber reinforced concrete (SFRC) becomes an issue due to the content of cementitious materials increased with the volume fraction of steel fiber. By using the expansive agent to reduce the shrinkage deformation of self-compacting SFRC, the strength reduction of hardened self-compacting SFRC is another issue. To solve these issues, this paper performed an experimental investigation on the workabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A very small increase in deformations, resulting from autogenous shrinkage in the material, can be observed between the first and seventh days of measurement. The gradients of all of the graphs are convergent, which confirms that the cause of deformation was autogenous shrinkage (to a large extent dependent on the amount of binder in the mix [38][39][40]). In the seven day period analysed, in comparison to the base concrete, the 2% and 4% additions of SRA caused 7% and 23% reductions in shrinkage, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…A very small increase in deformations, resulting from autogenous shrinkage in the material, can be observed between the first and seventh days of measurement. The gradients of all of the graphs are convergent, which confirms that the cause of deformation was autogenous shrinkage (to a large extent dependent on the amount of binder in the mix [38][39][40]). In the seven day period analysed, in comparison to the base concrete, the 2% and 4% additions of SRA caused 7% and 23% reductions in shrinkage, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…With short and random distributed steel fibers, a composite material is produced to be the steel fiber reinforced concrete (SFRC) [ 1 , 2 , 3 ]. This promotes the post-cracking performances of conventional concrete [ 4 , 5 , 6 , 7 ]. From the viewpoint of meso-mechanism, the bond of steel fiber is essential to the reinforcement effect, and the steel fibers bridging cracks of concrete matrix enhance the post-cracking performance of SFRC [ 2 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Shen et al, 2020) investigated the combined use of lightweight aggregate and an EA in UHPC and found that the expansive UHPC exhibited high levels of expansion and high mechanical properties. (Li et al, 2020) found that the compressive strength, splitting tensile strength and elastic modulus of self-compacting steel-fibre-reinforced concrete increased when an EA was incorporated. (Cao et al, 2017) observed that the compressive strength of expansive self-consolidating concrete was improved at 7 days when an EA was added.…”
Section: Introductionmentioning
confidence: 99%